Impairments in Episodic-Autobiographical Memory and Emotional and Social Information Processing in CADASIL during Mid-Adulthood - Staniloiu, Angelica; Woermann, Friedrich G.; Markowitsch, Hans J. (Frontiers in Behavioral Neuroscience, 2014)
CADASIL – Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy – is the most common genetic source of vascular dementia in adults, being caused by a mutation in NOTCH 3 gene. Spontaneous de novo mutations may occur, but their frequency is largely unknown. Ischemic strokes and cognitive impairments are the most frequent manifestations, but seizures affect up to 10% of the patients. Herein we describe a 47-year old male scholar with a genetically confirmed diagnosis of CADASIL (Arg133Cys mutation in the NOTCH3 gene) and a seemingly negative family history of CADASIL illness, who was investigated with a comprehensive neuropsychological testing battery and neuroimaging methods. The patient demonstrated on one hand severe and accelerated deteriorations in multiple cognitive domains such as concentration, long-term memory (including the episodic-autobiographical memory domain), problem solving, cognitive flexibility and planning, affect recognition, discrimination and matching, and social cognition (theory of mind). Some of these impairments were even captured by abbreviated instruments for investigating suspicion of dementia. On the other hand the patient still possessed high crystallized (verbal) intelligence and a capacity to put forth a façade of well-preserved intellectual functioning. Although no definite conclusions can be drawn from a single case study, our findings point out to the presence of additional cognitive changes in CADASIL in middle adulthood, in particular to impairments in the episodic-autobiographical memory domain and social information processing (e.g. social cognition). Whether these identified impairments are related to the patient‘s specific phenotype or to an ascertainment bias (e.g. a paucity of studies investigating these cognitive functions) requires elucidation by larger scale research.